Estudos estruturais e das interações com membranas de peptídeos antimocrobianos por RMN em solução e em fase sólida: análise conformacional e cálculos ab-initio de tensores de blindagem - Jarbas Magalhaes Resende (2008)
Phylloseptins are antimicrobial peptides of 19 to 20 residues which are found in the skin secretions of the Phyllomedusa frogs that inhabit the tropical forests of South and Central Americas. The focus of this PhD thesis concerns structural and membrane-interactions studies of the peptides phylloseptin 1, 2 and 3 (PS-1, PS-2 and PS-3). These peptides carry an amidated C-terminus and they exhibit 74% sequence homology with major variations of only four residues close to the C-terminus. Here are investigated and compared the structures of the three phylloseptins in detail by circular dichroism (CD) and two-dimensional nuclear magnetic resonance (NMR) spectroscopies in the presence of phospholipidvesicles or in membrane mimetic environments. Both CD and NMR spectroscopies reveal a high degree of helicity in the order PS-2 ? PS-1 > PS-3, where the main differences accumulate at the C-terminus. The conformational variations can be explained by taking into consideration electrostatic interactions of the negative ends of the helix dipoles with potentially cationic residues at positions 17 and 18. Whereas two are present in the sequence of PS-1 and -2, only one is present in PS-3. Furthermore, the additional role of hydrophobic interactions, hydrogen bonding, capping interactions and C-terminal amidationfor the stabilization of the helix and for antimicrobial action are discussed. Once amphipathic helical arrangements have been determined for thethree peptides by CD and solution NMR, these compounds (selectively labelled with 15N and 2H) were reconstituted into oriented phospholipid bilayers and solid-state NMR measurements were carried out. Although it is not possible to precisely determine the peptide orientation from 15N chemical shift or the 2H quadrupolar splitting alone, the two parameters furnished highly complementary topological restraints that have been used to obtain an accurate definition of the orientation of the peptides in the bilayers. Eventually, the 1H-15N dipolar splitting (obtained from PISEMA experiments) gave further topological restrains. PS-2and PS-3 adopt perfect in-plane alignments, which is in plain agreement with their amphipathic structures lying at the membrane interface. Despite the high amphipathic character of PS-1, the polar C-terminal Asn-19 residue at the hydrophobic side of the helix forces a small deviation of the helix main axis with regards to an in-plane orientation. The structural and topological differences observed for the three phylloseptins in membrane-mimicking environments can be correlated to an advanced innate immunological system of the animal, as the storage of cocktails of antimicrobials in the skin makes available a larger choiceand, therefore, a defense mechanism that works against many different microorganisms. At the same time releasing mixtures of antimicrobialcompounds allows for a synergistic action of combinations of peptides. Another part of this work comprises structural studies and shieldingconstant calculations by DFT (density functional theory) quantum methods. A strategy of peptide fragmentation aiming at a feasible molecular modelling of helical peptides has been proposed, and the obtained final structures have shown to be pretty similar to the ones obtained by solution NMR. A good agreement has been reached between experimental and theoretical chemical shifts and, therefore, the proposed strategy of molecular modelling proves to be a very promising tool in cases where problems like natural line-broadening or even other thermodynamic issues prevents the acquisition of good quality 2D NMR spectra.